STUDI KARAKTER KEPEMIMPINAN SERVANT TERHADAP MOTIVASI DAN PERILAKU KEWARGANEGARAAN ORGANISASI DI SEKTOR PUBLIK - Ramadhan, Muhamad Nur Rahmat; Kustiawan, Unggul (JURNAL CAFETARIA, 2024)
The world is currently facing increasing challenges and demands for better public service delivery, therefore the public sector plays an important role where people increasingly demand high quality services in their daily interactions with public organizations. This research aims to explore the factors that influence public sector workers, especially the encouragement of servant leadership towards organizational citizenship behavior, with the help of public servant motivation as an intervening variable that makes workers have OCB traits thanks to the encouragement of a leader. The data in this study was designed using a survey method where questionnaires were distributed online, and respondents were selected using a purposive sampling method in the DKI Jakarta area from public sector civil servants who had worked for more than two years. For analysis using factor analysis and structural equation modeling with the smartPLS application. This study's results show a positive relationship between servant leadership and, public service motivation, and organizational citizenship behavior. The managerial implication of this research is that organizations must always pay attention to their leaders so that employees feel how servant leadership behavior can improve and foster OCB attitudes and traits in each employee.